2008
DOI: 10.1097/ccm.0b013e318169245a
|View full text |Cite
|
Sign up to set email alerts
|

Serum neutrophil gelatinase-associated lipocalin (NGAL) as a marker of acute kidney injury in critically ill children with septic shock

Abstract: Objective-To validate serum neutrophil gelatinase-associated lipocalin (NGAL) as an early biomarker for acute kidney injury (AKI) in critically ill children with septic shock.Design-Observational cohort study. Setting-15 North American pediatric intensive care units (PICU).Patients-A total of 143 critically ill children with SIRS or septic shock and 25 healthy controls. Interventions-None.Measurements and Main Results-Serum NGAL was measured during the first 24 hours of admission to the PICU. AKI was defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
185
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(209 citation statements)
references
References 48 publications
19
185
1
4
Order By: Relevance
“…24 Similarly, serum NGAL and cystatin C have been found to be promising diagnostic biomarkers for early detection of AKI in a range of clinical settings, including cardiac surgery, contrast-induced nephropathy, and sepsis. [25][26][27][28][29] Acute kidney injury prognosis…”
Section: Acute Kidney Injury Predictionmentioning
confidence: 99%
“…24 Similarly, serum NGAL and cystatin C have been found to be promising diagnostic biomarkers for early detection of AKI in a range of clinical settings, including cardiac surgery, contrast-induced nephropathy, and sepsis. [25][26][27][28][29] Acute kidney injury prognosis…”
Section: Acute Kidney Injury Predictionmentioning
confidence: 99%
“…They concluded that urine NGAL is probably a more robust marker of AKI than plasma NGAL in patients with septic shock since urine NGAL levels remain within normal limits even when plasma levels are high and signs of AKI are absent. Previous studies on pediatric ICU patients have also shown that serum NGAL is a nonspecific predictor [19] and urine NGAL is a good predictor of AKI [13]. Bagshaw et al, also studied plasma and urine NGAL levels in early diagnosis of AKI in septic patients [15].…”
Section: Parametermentioning
confidence: 99%
“…It was shown previously in many clinical studies and has been accepted that NGAL and Cystatin C levels increase in different clinical settings leading to AKI development [10][11][12][13][14][15][16][17][18][19][20][21][22]. Since the aim of this study is to define the roles of Cystatin C and NGAL in predicting septic AKI development, the patients who had other risk factors, rather than sepsis, that would lead to AKI and increase the Cystatin C and NGAL levels (i.e., nonseptic-AKI patients) were excluded from the study.…”
Section: Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier study performed in critically ill children [11], it was demonstrated that pNGAL is increased in sepsis and septic shock even in the absence of AKI. This was not unexpected regarding the fact that NGAL is released from activated neutrophils.…”
mentioning
confidence: 94%